Tinjauan Prosedur Pendaftaran Pasien Rawat Inap di RSU Bhakti Asih Tangerang - Fandhika, Lilin Tata; Fannya, Puteri; Rumana, Nanda Aula; Yulia, Noor (Publikasi Indonesia, 2022)
The inpatient registration procedure contains a collection of patient data that is admitted per day, from the existing data registered for inpatient registration, it can be seen the number of patients admitted per day, the number of patients admitted per treatment room. The purpose of this study was to determine the procedure for registering inpatients at Bhakti Asih General Hospital, Tangerang. This type of research uses a qualitative descriptive method. Data collection techniques used are observation and interviews. The results of this study are related to the implementation of inpatient registration procedures, there are obstacles regarding incomplete requirements at the time of registration such as personal identity cards (KTP/KK), patient referral letters and the lack of registration officers so that there is a buildup during inpatient registration. the lack of completeness in the patient identity requirements as a condition for patient registration, therefore the officer must educate the patient to make a statement letter for files that are left behind 2 X 24 hours or before the patient goes home. to be brought as terms and procedures of patient registration at the hospital.